The influence of adolescents’ internet adaptation on internet addiction: the mediating role of internet cultural adaptation - Yang, Yue; Zhan, Jun; Ni, Yao; Fan, Yanwen; Zhang, Yiting; Fang, Yiting (Frontiers in Psychiatry, 2024)
This study investigates how adolescents’ internet adaptation influences internet addiction, with a particular focus on the mediating role of internet cultural adaptation. Grounded in cross-cultural adaptation theory, the study proposes that internet cultural adaptation can mitigate the negative relationship between internet adaptation and internet addiction. Conducting a large-scale random survey among Chinese adolescents, and employing standardized measures for internet addiction, internet cultural adaptation, and internet adaptation, the study finds a significant negative correlation between internet adaptation and internet addiction. More crucially, internet cultural adaptation plays a pivotal mediating role, such that when adolescents have higher capabilities in adapting culturally to the internet, the negative relationship between their internet adaptation and addiction is effectively alleviated. These findings not only provide a new perspective in understanding adolescent internet addiction but also offer theoretical guidance for devising preventive measures. The study also discusses practical applications of the results, emphasizing the importance of enhancing adolescents’ internet cultural adaptation, and presents new strategies for preventing and mitigating issues of internet addiction.